Miniaturized Multispectral Detector Derived from Gradient Response Units on Single MAPbX3 Microwire. Issue 9 (21st January 2022) - Xu, Xiaobao; Han, Zeyao; Zou, Yousheng; Li, Junyu; Gu, Yu; Hu, Dawei; He, Yin; Liu, Jiaxin; Yu, Dejian; Cao, Fei; Zeng, Haibo
Abstract: Miniaturized multispectral detectors are urgently desired given the unprecedented prosperity of smart optoelectronic chips for integrated functions including communication, imaging, scientific analysis, etc. However, multispectral detectors require complicated prism optics or interference/interferometric filters for spectral recognition, which hampers the miniaturization and their subsequent integration in photonic integrated circuits. In this work, inspired by the advance of computational imaging, optical‐component‐free miniaturized multispectral detector on 4 mm gradient bandgap MAPbX3 microwire with a diameter of 30 µm, is reported. With accurate composition engineering, halide ions in MAPbX3 microwire vary from Cl to I giving in the gradual variation of optical bandgap from 2.96 to 1.68 eV along axis. The sensing units on MAPbX3 microwire offer the response edge ranging from 450 to 790 nm with the responsivity over 20 mA W −1, −3dB width over 450 Hz, LDR of ≈60 dB, and a noise current less than ≈1.4 × 10 −12 A Hz −0.5 . As a result, the derived miniaturized detector achieves the function of multispectral sensing and discrimination with spectral resolution of ≈25 nm and mismatch of ≈10 nm. Finally, the proof‐of‐concept colorful imaging is successfully conducted with the miniaturized multispectral detector to further confirm its application in spectral recognition. Abstract : An optic‐component‐free miniaturized multispectral detector with response‐modulated photodetector units on gradient bandgap MAPbX3 microwire is fabricated to detect and discriminate incident light from 450 to 790 nm, with 25 nm resolution. This work will push multispectral detectors to universal application and provide guidance for forthcoming research in novel functional perovskite devices.